How do you simplify the expression #3(4(3x - 6) - 2(2x + 1))#?

1 Answer
Jul 29, 2016

Answer:

Use the distributive property to solve the problems in the parentheses.

Explanation:

The distributive property states that #a(b+c)=a*b+a*c#. Let's solve for the 2 problems in the parentheses first:

#4(3x-6)=4*3x+4*-6=12x-24#

#-2(2x+1)=-2*2x+ -2*1=-4x-2#

We now have #3(12x-24-4x-2)#.

Next, let's combine like terms:

#12x-4x=8x#

#-24-2=-26#

We now have #3(8x-26)#.

To get our answer, let's use the distributive property one more time:

#3(8x-22)=3*8x+3*-26=24x-78#

#24x-78# is our answer.